Presleep Ruminating on Intrusive Thoughts Increased the Possibility of Dreaming of Threatening Events - Feng, Xiaoling; Wang, Jiaxi (Frontiers in Psychology, 2022)
This study investigated whether ruminating on an intrusive thought before sleeping led to an increased likelihood of dreaming of threatening events. One hundred and forty-six participants were randomly assigned to a rumination condition (a rumination on an intrusive thought for 5min before sleeping; N = 73) and a control condition (think about anything for 5min before sleeping; N = 73). Participants completed a dream diary upon waking. The result showed that presleep ruminating on an intrusive thought increased the frequency of both threatening dreams and negative emotions in dreams. In addition, dreams with threatening events were more emotional and negative than dreams without threatening events. These results may support the threat simulation theory of dreaming (Ronvonsuo, 2000). In addition, these results may give some insight into Schredl's (2003; 2012) mathematical model for the continuity hypothesis of dreaming.